The development of molecular markers for Hevea breeding - Low F C; Atan Safiah; Jaafar Hafsah; Tan H (IRRDB symposium on physiological and molecular aspects of the breeding of Hevea brasiliensis 6-7 November 1995, 1995)
Four DNA molecular marker techiques are described. These are the classical hybridisation-based molecular marker technique called restriction fragment length polymorphisms (RFLPs) and three in vitro amplification-based techniques,namely random amplified polymorphic DNA (RAPD), microsatellites or simple sequence repeats (SSRs) and DNA amplification fingerprinting (DAF). These molecular markers were able to elicit interspecific polymorphisms. They were also able to assist in sveral identification studies. Cultivars wich share two common parents (siblings), such as PR 255 and PR 261 ; RRIM 901 and RRIM 905 ; and RRIM 937 and RRIM 938, have been distinguished by their DNA polymorphisms. Similarly, molecular markers have assisted in the identification of rouges in a sample of monoclonal PB 5/51 seedilings. The genetic diversity of genotypes from the 1981 IRRDB Hevea germplasm collectio from Brazil was also demonstrated by their RFLPs. DNA fingerprinting techniques such as SSR and DAF have elicited somaclonal variants among a population of GL 1 plants derived from anther and ovule culture. A genetic linkage map comprising of RFLPs and other markers is being attempted. The strength and limitations of these marker techniques are discussed and compared.
Keywords: Breeding; DNA fingerprinting; Hevea; molecular markers; RAPD; RFLP; Simple sequence repeats (SSRs)